Sumber Daya Manusia dan Pertumbuhan Ekonomi Regional di Provinsi Maluku, 2003-2007 (Studi Kasus Data Panel) - Yerimias Manuhutu (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2010)
The aim of this study is to analyze and examine the affect of human resources on regional economic growth in Province of Maluku by using the data of 8 regions for periods 2003-2007. Estimation method used in this research is panel data by applying fixed effect. Factors that affect economic growth are human resources which human capital (government and pivate investments in education), investment, labour force, and the population. The results of the study show that regional economic growth for periods 2003-2007 in Province of Maluku is influenced by human resources and labor force positively and significant. The population is affecting negatively and not significant. Investment is influenced by regional economic growth positively but not significant. Keywords: human resouces, economic growth, investment in education, GDRP